PENGARUH PENDIDIKAN, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHDAP KINERJA KARYAWAN CV. INDORIZVA SAWAHAN NGANJUK - Anggraini, Farida Dwi; Arifin, Zainal; Surindra, Bayu (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by a lack of education, a high workload and a work environment that does not support the performance of CV employees Indorizva Sawahan Nganjuk. This study uses a quantitative approach with causal techniques, Collecting data using questionnaires, documentation, literature study. The sample of this study used a saturated sampling technique covering 18 employees. The analysis in this study used multiple linear regression. The results of the research on the test are:1) education has no effect on employee performance with a single value of 0.199 > 0.05. 2) The workload has an influence on employee performance with a sign value of 0.037 <0.05. 3) The work environment has an influence on employee performance with a sign value of 0.034 <0.05. 4) education (X _1), workload (X _2), and work environment (X _3) simultaneously affect employee performance with F_hitung 17.415 and sign value 0.000